1968
DOI: 10.1073/pnas.61.1.138
|View full text |Cite
|
Sign up to set email alerts
|

"Big insulin": a new component of plasma insulin detected by immunoassay.

Abstract: Since the advent of radioimmunoassay, I the concentration of insulin in plasma of normal and diabetic subjects in response to many stimuli has been studied extensively.2 However, the chemical nature of the circulating hormone is not entirely clear. We find that endogenous plasma insulin has two components.One is very similar to pancreatic insulin. The other component is larger in size and immunologically less reactive than pancreatic insulin. With our antiserum, it accounts for up to 50 per cent of plasma insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

1969
1969
1985
1985

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(69 citation statements)
references
References 13 publications
4
65
0
Order By: Relevance
“…Clark and Steiner in a prior publication reported such an in vitro action for glucose (8). A "big insulin" in human and animal plasmas has been described (9). Though not conclusively proven, it seems likely that this material is indeed proinsulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark and Steiner in a prior publication reported such an in vitro action for glucose (8). A "big insulin" in human and animal plasmas has been described (9). Though not conclusively proven, it seems likely that this material is indeed proinsulin.…”
Section: Introductionmentioning
confidence: 99%
“…Though not conclusively proven, it seems likely that this material is indeed proinsulin. Efforts to specifically identify and measure proinsulin in the plasma have been Received for publication 8 September 1969 and in revised form 16 October 1969. hampered by technical problems such as lack of human proinsulin standards and the likelihood that the antigenic "connecting peptide" of proinsulin is also in the circulation and must be differentiated from intact proinsulin (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…This subject was critically reviewed by Berson and Yalow in 1966 (14), and they concluded that there was very little to support these alternative views. However, since 1966 two laboratories (15,16) have published evidence for substances of greater molecular weight than insulin, which react with anti-insulin antibody, but which appear to have a lessened biological activity. In addition, several groups of workers (17)(18)(19) (17,18) or the fasting insulin level (19).…”
Section: Introductionmentioning
confidence: 99%
“…Proinsulin, the single-chain polypeptide precursor of insulin, has been identified in human (1)(2)(3)(4)(5)(6), bovine (7,8), transaminase was assayed (18) in the initial and final perfusate sample from each experiment. The values were below 10 IU and did not increase significantly in the latter samples.…”
Section: Introductionmentioning
confidence: 99%